Supramolecular framework membrane for precise sieving of small molecules, nanoparticles and proteins - Zhang, Guohua; Li, Xinyue; Chen, Gang; Zhang, Yue; Wei, Mingfeng; Chen, Xiaofei; Li, Bao; Wu, Yuqing; Wu, Lixin (Nature communications, 2023)
Synthetic framework materials have been cherished as appealing candidates for separation membranes in daily life and industry, while the challenges still remain in precise control of aperture distribution and separation threshold, mild processing methods, and extensive application aspects. Here, we show a two-dimensional (2D) processible supramolecular framework (SF) by integrating directional organic host-guest motifs and inorganic functional polyanionic clusters. The thickness and flexibility of the obtained 2D SFs are tuned by the solvent modulation to the interlayer interactions, and the optimized SFs with limited layers but micron-sized areas are used to fabricate the sustainable membranes. The uniform nanopores allow the membrane composed of layered SF to exhibit strict size retention for substrates with the rejection value of 3.8 nm, and the separation accuracy within 5 kDa for proteins. Furthermore, the membrane performs high charge selectivity for charged organics, nanoparticles, and proteins, due to the insertion of polyanionic clusters in the framework skeletons. This work displays the extensional separation potentials of self-assembled framework membranes comprising of small-molecules and provides a platform for the preparation of multifunctional framework materials due to the conveniently ionic exchange of the counterions of the polyanionic clusters. Synthetic framework materials are appealing candidates for the fabrication of separation membranes but realizing precise control of aperture distribution and separation threshold remains challenging. Here, the authors show a two-dimensional processible supramolecular framework which can be used in the fabrication of separation membranes by integrating directional organic host-guest motifs and inorganic functional polyanionic clusters.